Cooperative interaction of hepatocyte growth factor and neuregulin regulates Schwann cell migration and proliferation through Grb2‐associated binder‐2 in peripheral nerve repair. Issue 11 (19th July 2017) - Shin, Yoon Kyoung; Jang, So Young; Yun, Seoug Hoon; Choi, Yun Young; Yoon, Byeol‐A; Jo, Young Rae; Park, So Young; Pak, Min Gyoung; Park, Joo In; Park, Hwan Tae
Abstract: The sequential reactive changes in Schwann cell phenotypes in transected peripheral nerves, including dedifferentiation, proliferation and migration, are essential for nerve repair. Even though the injury‐induced migratory and proliferative behaviors of Schwann cells resemble epithelial and mesenchymal transition (EMT) in tumors, the molecular mechanisms underlying this phenotypic change of Schwann cells are still unclear. Here we show that the reactive Schwann cells exhibit migratory features dependent on the expression of a scaffolding oncoprotein Grb2‐associated binder‐2 (Gab2), which was transcriptionally induced by neuregulin 1‐ErbB2 signaling following nerve injury. Injury‐induced Gab2 expression was dependent on c‐Jun, a transcription factor critical to a Schwann cell reprograming into a repair‐type cell. Interestingly, the injury‐induced activation (tyrosine phosphorylation) of Gab2 in Schwann cells was regulated by an EMT signal, the hepatocyte growth factor‐c‐Met signaling, but not by neuregulin 1. Gab2 knockout mice exhibited a deficit in nerve repair after nerve transection due to limited Schwann cell migration. Furthermore, Gab2 was required for the proliferation of Schwann cells following nerve injury and in vitro, and was over‐expressed in human Schwann cell‐derived tumors. In contrast, the tyrosine phosphorylation of Gab1 after nerve injury was principally regulated by the neuregulin 1‐ErbB2 signaling and was indispensable for remyelination after crush injury, but not for the proliferation and migration of Schwann cells. Our findings indicate that Gab1 and Gab2 in Schwann cells are nonredundant and play a crucial role in peripheral nerve repair. Main Points: Injury‐induced plastic changes of Schwann cells are essential for peripheral nerve repair. Grb2‐associated binder‐2 mediates neuregulin and hepatocyte growth factor signaling to promote Schwann cell migration and proliferation during nerve repair.